Interchange experience in Portugal: perspective for research - Dantas, Rosane Arruda; Pagliuca, Lorita Marlena Freitag (Rev Rene, 2004)
Experience about an interchange program of a graduation nursing student, who is also a scholar of the National Council of Research and Technology (CNPq), in Porto, Portugal, in April 2001. First I checked the opportunities available at the UFC Medicine Academic Center, but I made the interchange possible through a contact between my professor and a friend of hers in that country. Al the Nursing College I participated in a debate about transculturality  and in another one about death and dying; in activities at the Students Association, in a meeting about “Basic Health Care” and in a visit to a hospital and to a Health Center. It is about the importance of the interchange program for the student and the relationship between government, private companies, and research public institutions.